The Omnis Barbaria Experimental Archaeology Camp for Children – First Edition - Marius Ardeleanu (EXARC, 2017)
Like in many other European countries, during the past 15 years, Romania has seen an increased interest by archaeologists and history enthusiasts towards the reconstruction of artefacts and certain phenomenal aspects of the past. Whether the study approached a theoretical (Sima 2002, 77-82; Barbu 2015, 779-793) or practical aspect, such as reconstruction of housing (Cotiugă 2009, 303-342), workshops (Ardeleanu 2012, 72-73), ritual pits (Ardeleanu 2015, 59-96), textiles (Torcică 2015, 219-230), stonework (Zăgreanu 2010, 361-363) or weapons (Borangic 2007-2008, 44-62; Borangic 2013, 821-836; Borangic, Barbu 2013, 22-47) all these archaeological experiments were conducted in order to find out and partially explain some issues of history that would otherwise remain unknown to researchers or to the general public.